Structural Health Monitoring, Photogrammetry & DIC, Volume 6 Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics 2018 - Niezrecki, Christopher; Baqersad, Javad (Conference Proceedings of the Society for Experimental Mechanics Series,, 2019)
Structural Health Monitoring Photogrammetry & DIC, Volume 6: Proceedings of the 36th IMAC, A Conference and Exposition on Structural Dynamics, 2018, the sixth volume of nine from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Health Monitoring & Damage Detection, including papers on: Structural Health Monitoring Damage Detection System Identification Active Controls.